2018
DOI: 10.1038/s41433-018-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography features of choroidal neovascularization secondary to angioid streaks

Abstract: Purpose To characterize the features of choroidal neovascularization (CNV) secondary to angioid streaks (AS) with optical coherence tomography angiography (OCT-A) and to assess its sensitivity in CNV detection in this particular context. Methods Consecutive patients, both with treatment-naïve and recurrent CNV associated with angioid streaks were prospectively analyzed. All patients underwent macular imaging by fluorescein angiography (FA), indocyanine green angiography (ICGA), spectral-domain (SD)-OCT, and OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Therefore, considering a potential relation between CSC and angioid streaks, we must focus on their pathophysiology. Recent studies using OCTA highlighted the choriocapillaris rarefaction on OCTA in patients with AS without CNV, interpreting this finding as an eventual atrophy of this vascular layer, associated with the overlying crack-like breaks in a thickened BM [5][6][7]. In particular cases, they described an irregular vascular network in the choriocapillaris in areas affected with AS, presenting a flat elevation of the RPE and hyperreflective accumulations between the BM and RPE on simultaneous structural SD-OCT [5].…”
Section: Discussion/ Conclusionmentioning
confidence: 99%
“…Therefore, considering a potential relation between CSC and angioid streaks, we must focus on their pathophysiology. Recent studies using OCTA highlighted the choriocapillaris rarefaction on OCTA in patients with AS without CNV, interpreting this finding as an eventual atrophy of this vascular layer, associated with the overlying crack-like breaks in a thickened BM [5][6][7]. In particular cases, they described an irregular vascular network in the choriocapillaris in areas affected with AS, presenting a flat elevation of the RPE and hyperreflective accumulations between the BM and RPE on simultaneous structural SD-OCT [5].…”
Section: Discussion/ Conclusionmentioning
confidence: 99%
“…7 OCT-A findings demonstrated a close correlation between CNV and AS, with neovascular lesions developing at the level of the streak path. 5…”
Section: Discussionmentioning
confidence: 99%
“…OCT-A showed a good sensitivity detecting CNV in AS, non-invasively. 4,5 It should be integrated into the standard imaging assessment of AS with neovascular complication and monitoring treated CNV evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Angioid streaks may be asymptomatic, but the development of macular neovascularization (MNV), occurring in approximately 42% to 86% of patients during follow-up, and macular atrophy, contributes to severe visual impairment in these patients [3,4]. Moreover, the onset of secondary MNV complicating angioid streaks occurs in the working age population, within the 5th decade according to recent literature [4,5]. While the prevalence of MNV and atrophy is directly proportional to the patients' age, it has recently been shown that in patients with pseudoxanthoma elasticum, eyes with longer angioid streaks (i.e., more extensive calcification of Bruch's membrane) have a higher risk of developing neovascularization or atrophy, and thereby will have a worse visual prognosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal imaging can help identifying foveal or extrafoveal neovascularization associated with angioid streaks. Optical coherence tomography angiography (OCTA) has been shown to be useful not only in the detection of neovascular complications in patients with angioid streaks, but also in evaluating MNV activity [4,5]. Furthermore, OCTA may also help the clinicians gain insight into the very determinants of neovascularization and macular atrophy.…”
Section: Introductionmentioning
confidence: 99%